Introduction (Scottish Historical and Archaeological Internet Reports, 2009)
Dunasbroc was chosen for further investigation because it was threatened by further erosion, and had already produced both Neolithic and Iron Age pottery, but it was relatively easy to access. Excavation aims and methodology are outlined in this section.